Proceedings of the Tenth Annual ACM/IEEE International Conference on Human-Robot Interaction 2015
DOI: 10.1145/2696454.2696458
|View full text |Cite
|
Sign up to set email alerts
|

Sacrifice One For the Good of Many?

Abstract: Moral norms play an essential role in regulating human interaction. With the growing sophistication and proliferation of robots, it is important to understand how ordinary people apply moral norms to robot agents and make moral judgments about their behavior. We report the first comparison of people's moral judgments (of permissibility, wrongness, and blame) about human and robot agents. Two online experiments (total N = 316) found that robots, compared with human agents, were more strongly expected to take an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(91 citation statements)
references
References 36 publications
4
84
2
1
Order By: Relevance
“…These studies point out, that the general population seems to favor utilitarian decisions (Bonnefon et al, 2015;Li et al, 2016;Malle et al, 2015). This applies even to cases, where the driver has to sacrifice himself for the greater good (Sachdeva, Iliev, Ekhtiari, & Dehghani, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies point out, that the general population seems to favor utilitarian decisions (Bonnefon et al, 2015;Li et al, 2016;Malle et al, 2015). This applies even to cases, where the driver has to sacrifice himself for the greater good (Sachdeva, Iliev, Ekhtiari, & Dehghani, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies were conducted, given the assumption that passengers would like ADVs to behave similarly to humans (Goodall, 2014;Malle, Scheutz, Arnold, Voiklis, & Cusimano, 2015;Sikkenk & Terken, 2015). They found that many factors drastically influence human behavior in traffic, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While to err is understood to be human, it is unclear how tolerant society is to machines making the wrong decisions. It appears that machine decision-making is held to a higher standard than human decision-making [10]. One reason for this could be that certain justifications for making a decision, such as empathy, feeling distracted or confused, are only valid arguments or "excuses" for people and do not apply to machines.…”
Section: Ethical Decision By Ai Systemsmentioning
confidence: 99%
“…Just because it is acceptable for a human to sacrifice another human for a greater good does not mean that a robot should make the same decision. Humans may put different blame on a robot than on a human for making the same decision in the same scenario [27]. How the model of decision-making I am developing can account for these recent results is beginning to be investigated.…”
Section: Models Of Moral Decision-makingmentioning
confidence: 99%